TactileAloha: Learning Bimanual Manipulation With Tactile Sensing - Gu, Ningquan; Kosuge, Kazuhiro; Hayashibe, Mitsuhiro (IEEE robotics and automation letters, 2025)
Tactile texture is vital for robotic manipulation but challenging for camera vision-based observation. To address this, we propose TactileAloha, an integrated tactile-vision robotic system built upon Aloha, with a tactile sensor mounted on the gripper to capture fine-grained texture information and support real-time visualization during teleoperation, facilitating efficient data collection and manipulation. Using data collected from our integrated system, we encode tactile signals with a pre-trained ResNet and fuse them with visual and proprioceptive features. The combined observations are processed by a transformer-based policy with action chunking to predict future actions. We use a weighted loss function during training to emphasize near-future actions, and employ an improved temporal aggregation scheme at deployment to enhance action precision. Experimentally, we introduce two bimanual tasks: zip tie insertion and Velcro fastening, both requiring tactile sensing to perceive the object texture and align two object orientations by two hands. Our proposed method adaptively changes the generated manipulation sequence itself based on tactile sensing in a systematic manner. Results show that our system, leveraging tactile information, can handle texture-related tasks that camera vision-based methods fail to address. Moreover, our method achieves an average relative improvement of approximately 11.0% compared to state-of-the-art method with tactile input, demonstrating its performance.